IMPACT OF A STRUCTURED SELF-CARE EDUCATIONAL MODULE ON GESTATIONAL DIABETES MELLITUS MANAGEMENT IN PESHAWAR, PAKISTAN (The Research of Medical Science Review, 2025)
Gestational Diabetes Mellitus (GDM) poses significant risks to maternal and neonatal health, particularly in South Asian populations. This study evaluates the impact of a structured self-care educational module on key health behaviors among pregnant women with GDM in Peshawar, Pakistan. A quasi-experimental design was conducted with 220 participants (110 intervention, 110 control). The intervention group received structured education, while the control group continued routine care. Pre- and post-intervention assessments measured knowledge, dietary adherence, glucose monitoring, physical activity, sleep quality, and psychological well-being. Results showed significant improvements in the intervention group: knowledge (45% to 90%), dietary adherence (45% to 85%), glucose monitoring (50% to 92%), and physical activity (35% to 88%). Stress reduction and sleep quality also improved (p<0.05). Findings support integrating structured education into antenatal care to enhance GDM self-management, particularly in resource-limited settings. Future research should assess long-term adherence and explore digital health solutions for patient education.